Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.725
|View full text |Cite
|
Sign up to set email alerts
|

Smart Application Development for IoT Asset Management Using Graph Database Modeling and High-Availability Web Services

Abstract: The rapid transition from purely physical or purely virtual systems, as we know them, to increasingly interconnected cyber-physical systems with high integration of the Internet-of-Things demands a paradigm shift in the development of information systems-smart applications-for the planning and operation of these systems. To address the demand of managing the integration of connected devices and enabling new business models from the heavily interconnected systems, current architectural reference models were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Finally, it can be observed that the SGAM is now also applied beyond Europe. Examples include application development for device management and control as well as system state monitoring for residential demand response ancillary services based on graph database modeling and high-availability web services in the USA [73], the development of an effective but efficient approach to risk assessments for Smart Grid projects in Australia [55] and modeling an off-grid rural village microgrid as a multi-agent nodal system and therefore formulating distributed market-based transactive control as a discrete-time system in South Africa/the USA [74].…”
Section: Further Projects Activities and Applicationsmentioning
confidence: 99%
“…Finally, it can be observed that the SGAM is now also applied beyond Europe. Examples include application development for device management and control as well as system state monitoring for residential demand response ancillary services based on graph database modeling and high-availability web services in the USA [73], the development of an effective but efficient approach to risk assessments for Smart Grid projects in Australia [55] and modeling an off-grid rural village microgrid as a multi-agent nodal system and therefore formulating distributed market-based transactive control as a discrete-time system in South Africa/the USA [74].…”
Section: Further Projects Activities and Applicationsmentioning
confidence: 99%
“…Today's popular social sites such as Facebook, Twitter, and Instagram use graphs to model relationships, which greatly speeds up queries about individual relationships, and network maintenance provides a unified interface for fast and efficient storage of relations. Furthermore, they are playing an increasing role in other areas of IT, such as telecommunications [8], road network infrastructure [9], and the organization of public transport routes [10]. In addition, they are gaining ground, for example, in biology, ref.…”
Section: Introductionmentioning
confidence: 99%